2010
DOI: 10.1146/annurev-neuro-060909-153230
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Human Prefrontal Cortex in Social Cognition and Moral Judgment

Abstract: Results from functional magnetic resonance imaging and lesion studies indicate that the prefrontal cortex (PFC) is essential for successful navigation through a complex social world inundated with intricate norms and moral values. This review examines regions of the PFC that are critical for implicit and explicit social cognitive and moral judgment processing. Considerable overlap between regions active when individuals engage in social cognition or assess moral appropriateness of behaviors is evident, undersc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
229
3
5

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 295 publications
(251 citation statements)
references
References 114 publications
(136 reference statements)
5
229
3
5
Order By: Relevance
“…In monkeys, damage to the OFC causes social-interaction deficits, such as a decrease in communicative facial expressions, reduced responses to threatening or affiliative gestures, and impaired development of maternal bonding (10). In humans, damage to the OFC is associated with personality changes and socially inappropriate behavior (11)(12)(13), and with impairments in the expression of social emotions, such as attachment, fear, and aggression (14,15). Notably, it has been suggested that the OFC is involved in valuation mechanisms in social context and contributes to decision making based on social reputation and trust (16), and in the generation of emotions, such as anticipated regret (17,18).…”
mentioning
confidence: 99%
“…In monkeys, damage to the OFC causes social-interaction deficits, such as a decrease in communicative facial expressions, reduced responses to threatening or affiliative gestures, and impaired development of maternal bonding (10). In humans, damage to the OFC is associated with personality changes and socially inappropriate behavior (11)(12)(13), and with impairments in the expression of social emotions, such as attachment, fear, and aggression (14,15). Notably, it has been suggested that the OFC is involved in valuation mechanisms in social context and contributes to decision making based on social reputation and trust (16), and in the generation of emotions, such as anticipated regret (17,18).…”
mentioning
confidence: 99%
“…This theory has been supported by brain imaging data which have identified that during moral decision-making tasks the "executive brain center" -prefrontal cortex -is associated with rational processing (Forbes & Grafman, 2010; whereas emotional regions including anterior temporal lobes and anterior cingulate gyrus are involved in emotional processing (Robertson et al, 2007). In addition, patients with fronto-temporal lobe dementia or ventromedial prefrontal cortex damage who have noted emotional deficits, have also shown more utilitarian responses (Ciaramelli, Muccioli, Ladavas, & di Pellegrino, 2007;Koenigs et al, 2007;Moretto, Ladavas, Mattioli, & di Pellegrino, 2010).…”
Section: Introductionmentioning
confidence: 88%
“…Although population research has established robust effects of poverty and inequality on these outcomes (37)(38)(39)(40)(41)(42), neural mechanisms of these effects have not been a primary focus in population approaches. However, within neuroscience and health psychology, research has begun to show that early life experiences such as parenting and SES have effects on brain areas such as the amygdala and prefrontal cortex (43)(44)(45)(46)(47), areas that have also been linked to a variety of relevant outcomes such as crime and violence (48,49), depression (50), social cognition (51,52), drug use (53,54), and cognitive control (55). For example, a recent study demonstrated that early life stress predicted stress responses in the hypothalamicpituitary-adrenal axis, which in turn predicted connectivity between the amygdala and prefrontal cortex and later risk for depression (56).…”
Section: Current Practices In Neuroimagingmentioning
confidence: 99%